How internal venture groups innovate Byron L. David finds that new-product ventures are most successful when they involve someone who is both the intrapreneur and the venture manager - David, Byron L. (Research management (Now: research technology management))
Product innovation by internal venturing is influenced by the mode of venturing you choose and the relationship between intrapreneurs, venture managers and the R&D functions.